Joint inventory replenishment planning of an e-commerce distribution system with distribution centers at producers' locations - Bo Dai; Fenfen Li (Logistics, 2021)
In this study, joint inventory replenishment planning of an Alibaba distribution system is investigated, which contributes to the circular economy concept. The distribution system includes suppliers, central distribution centers, and front distribution centers. The total replenishment cost of the distribution system can be reduced by setting up distribution centers at producers' locations (PDCs), which also helps to reduce the wastages of commodities during the transportation and CO2 emission released by transportation. The joint replenishments of multiple products are constrained by a maximum joint replenishment quantity. Trans-shipments happen among different distribution centers. The considered problem seeks to find the replenishment quantities of products among stocks, which can minimize the total replenishment cost of the system, and is formulated as a novel mathematical model. The effectiveness of our proposed model is validated by computational experiments based on Alibaba's data. The results indicate that PDCs and trans-shipments can bring about lower replenishment costs if a common service level of the system is given.
Keywords: 650; inventory management; e-commerce; distribution systems; optimization; circular economy; CO2 emission; distribution centers at producers' locations